Rediscovery of the holotype of Horvathinia lenti De Carlo, 1958, new junior synonym of H. pelocoroides Montadon, 1911 (Insecta: Hemiptera: Belostomatidae) - Rodrigues, Claudia L.; Braga, Rafael B.; Moreira, Felipe F. F. (Zootaxa, 2020)
Horvathinia pelocoroides Montandon, 1911 was described as a new genus and species based on two specimens collected in Brazil, one from Minas Gerais deposited in the Naturhistoriska Riksmuseet (Stockholm) and the other from Rio Grande do Sul deposited in the Magyar Természettudományi Múzeum (Budapest) (Montandon 1911). Subsequently, nine additional species were described based on a single specimen each, collected at different localities in southern South America: H. doellojuradoi De Carlo, 1930; H. pelleranoi De Carlo, 1930; H. castilloi De Carlo, 1938; H. meyeri De Carlo, 1938; H. bollei De Carlo, 1958; H. lenti De Carlo, 1958; H. schubarti De Carlo, 1958; H. forsteri Lauck, 1958; and H. argemii Schnack, 1972 (Schnack & Estévez 2005).